1973
DOI: 10.2134/agronj1973.00021962006500040001x
|View full text |Cite
|
Sign up to set email alerts
|

Rice Responses to Nitrogen Under High Solar Radiation and Intermittent Flooding in Peru1

Abstract: The purpose of this study was to characterize the varietal responses of rice (Oryza sativa L.) to N fertilization in a tropical desert climate where extremely high N application rates are needed to attain maximum yields. Eight rice cultivars of contrasting plant type and growth duration were tested at applied N levels of 0 to 480 kg N/ha in a field experiment with an intermittently flooded water regime. Among the semi‐dwarf cultivars, the earlier maturing ‘IR8x2019; produced a maximum yield of 11.7 ton/ha at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Green manure density Green manure duration Fallow with vs. without inorganicN above this ratio ( Table 5). Examination of the original reports surveyed by van Keulen and van Heemst (1982) showed that, for rice, the ratio exceeded 0.075 Mg kg-1 N in two cases (Williams et al, 1972;Sanchez et al, 1973). However, ratios closer to 0.070 Mg kg-1 N were more common.…”
Section: Sources Of Variation Df Grain Yield N Uptake ---F•ratiomentioning
confidence: 98%
“…Green manure density Green manure duration Fallow with vs. without inorganicN above this ratio ( Table 5). Examination of the original reports surveyed by van Keulen and van Heemst (1982) showed that, for rice, the ratio exceeded 0.075 Mg kg-1 N in two cases (Williams et al, 1972;Sanchez et al, 1973). However, ratios closer to 0.070 Mg kg-1 N were more common.…”
Section: Sources Of Variation Df Grain Yield N Uptake ---F•ratiomentioning
confidence: 98%
“…Response of grain yield to N rate varied with genotype in Experiment 1 (dry season) such that yield in the early-maturing genotypes (Newbonnet and Lemont) was more responsive to N rates >70 kg/ha than in the late-maturing genotype (Starbonnet). Similarly, Sanchez et al . (1973) found that within a specific rice plant type in Peru, the earlier maturing genotype produced a higher grain yield in response to N than its later maturing counterpart, suggesting that early maturity increases the responsiveness of grain yield to N in a high solar radiation environment.…”
Section: Effect Of Plant Typementioning
confidence: 64%
“…Generally, short-statured and earlymaturing genotypes are more responsive to N than tall-statured and late-maturing genotypes (De Datta et al . 1968;Sanchez et al . 1973;De Datta and Malabuyoc 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a better control of lodging, this is because modern varieties require considerably less nitrogen per kg grain yield than traditional varieties, but take up nitrogen at least as efficiently (cf. Sanchez et al, 1973). This increased efficiency is a general phenomenon because it is directly related to the much better seed/straw ratios of modern varieties compared with traditional ones.…”
Section: Why Yields Continue To Increasementioning
confidence: 99%